Intra Articular Injection of Mesenchymal Stem Cells in Osteoarthritis of the Knee Joint: A Systematic Review - Ilham Hariaji (Universitas Muhammadiyah Sumatera Utara, 2022)
Abstract: Treatment of osteoarthritis in the knee joint is carried out by sharing efforts. In addition to pharmacological therapy, it is also carried out therapy with the method of intra-articular injection of mesenchymal stem cells directly into the knee joint. This systematic study aims to find out the extent to which this method has been studied as well as the benefits of intra-articular knee joint by means of mesenchymal stem cells. This study was conducted as a systematic study by searching journal literature through the Google Scholar application with the keyword intra articular injection mesenchymal stem cells on knee osteoarthritis in the last 5 years, using a prism diagram classification system in article selection. The results of the selection found 41 articles that were included in the inclusion criteria. The results of the study found that there have been many studies of intra-articular injection therapy of mesenchymal stem cells from various sources. Research was carried out both pre-clinical and clinical, and assessment methods were carried out with various methods to see the results of the therapy given, and 90% showed the results of structural, functional, and clinical improvement of the knee joint. From the results of these studies, it is concluded that there have been many studies conducted and most have shown that this method provides benefits.